Regenerative endodontic procedures in immature permanent teeth with pulp necrosis: the impact of microbiology on clinical and radiographic outcome - Sellami, Rayann; Van Holm, Wannes; Meschi, Nastaran; Van Den Heuvel, Sarah; Pauwels, Martine; Verspecht, Tim; Vandamme, Kathleen; Teughels, Wim; Lambrechts, Paul (Frontiers in Dental Medicine, 2023)
The current study aimed to determine how the regenerative endodontic procedures (REP) disinfection strategy influences overall bacterial load and REP outcomes. Different bacterial species in the teeth were also examined.A previously reported non-randomized controlled clinical research on REP+/-leukocyte and platelet rich fibrin gathered microbial samples from 14 of 29 patients during REP (LPRF). Four microbiological samples were obtained in two treatment session. S1 and S2 were taken before and after the first irrigation with 1.5% NaOCl and saline. Samples S3 and S4 were obtained before and after rinsing with 17% EDTA in the second treatment session. Microbial samples were identified using qPCR with species-specific primers.The total bacterial load recovered from patients showed a significant (p<0.05) decrease after the first treatment and was maintained throughout the second treatment. F. nucleatum, T. denticola and E. faecalis were the most prevalent species in root canals, detected in all analyzed cases (100%), followed by P. intermedia and T. forsynthia, both in 6 of 14 cases (42.9%). The presence of these abundant species was significantly reduced after S1. P. micra was present in 4 of 14 cases (28.6%) and A. naeslundii in 2 of 14 cases (14.3%). F. alocis, P. endodontalis and P. gingivalis were each only detected only in 1 of 14 cases (7.1%). No statistical correlation could be made between bacterial species and clinical or radiographic outcome due to the small sample size. In the LPRF-group 2 cases required retreatment due to early post treatment flare-up and 2 other cases presented radiographically a persistent apical periodontitis 3 years post treatment. In the control group all analyzed cases were clinically asymptomatic post treatment and radiographically the final periapical index score at the last recall revealed healthy periapices.The REP disinfection protocol of the current study seems to be effective enough to reduce the total bacterial load, to omit clinical symptoms and to induce periapical bone healing in immature permanent teeth with pulp necrosis. LPRF seems to prevent that and should consequently not be recommended in REP.